Temperature Dependent Mechanical Characterisation of Styrene-Acrylonitrile - GÜLLÜOĞLU, ARİF NİHAT (RAPRA TECHNOLOGY LTD, 2009)
Poly(styrene-co-acrylonitrile) (SAN) which is a random, amorphous, linear copolymer produced by copolymerising styrene and acrylonitrile was investigated experimentally. Specimens were supplied from a private company and they were analysed using a differential scanning calorimetry machine (DSC). The behaviour of the material in creep, tension and hardness experiments was investigated experimentally at several temperatures. The creep response of SAN was also evaluated.
Keywords: DENSITY POLYETHYLENE PIPE; CREEP-BEHAVIOR; BLENDS